ANALISIS KANDUNGAN ZAT GIZI SOUN GANYONG (Canna edulis) DAN DAYA TERIMA KONSUMEN - Trimurti Artama; Eko Yuliastuti E.S (LPPM Universitas Terbuka, 2006)
Food resistance will be strengthened with diversity of food products. In order to augment raw materials for soun, a variety of white starch noodle, a research was conducted using starch of ganyong (Canna edulis). The purpose of the research was to survey the nutrient content and consumer acceptance of soun ganyong. Nutrient content was analyzed by proximate method and consumer acceptance was analyzed by organoleptic test. The result showed that carbohydrate content was 83.86% to 85.12% higher than the carbohydrate of white rice, main food supply of the population. Therefore, it can be suggested that soun ganyong be used as supplement for the carbohydrate food supply. The organoleptic test showed that consumers prefer (acceptability) the color, taste, and aroma of the white variety than the blue one, while the texture for both varieties was generally accepted.